The Impact of Creative Writing on Foreign Language ( English) Proficiency Development - Birsen Tütüniş; Selin Küçükali (Informascope, 2014)
Writing in English as a foreign language is a skill which needs to be developed for full proficiency. In writing classes however, students feel anxious and show a negative attitute towards writing. Creative writing activities in foreign language classes might bring some solutions both to writing teachers' difficulties and to students who look down upon writing as a class activity. Creative writing does not require a model to dublicate the prescribed patterns. Creative writing helps students to involve personally and enjoy the writing process . While writing, students are not aware of the progress they make for full proficiency. The education system in Turkey requires the curriculum to be covered; learning is dictated and  personal freedom is ignored. However, university level students need to build the capacity to comment on any kind of topic that they may come across during their lifetime. A system which encourages the students to do creative writing both in L1 and in L2 would allow them to realize their own linguistic skills. There is always a need for creative people who can improve themselves and make contributions to their environment. This paper aims to show whether creative writing based EFL classes at tertiary level would be effective in the improvement of writing skills of the students.